GREEN PERCEIVED VALUE, GREEN SATISFACTION, GREEN TRUST TOWARDS UNILEVER CONSUMER GREEN LOYALTY - Wardani, Salsabilah Herman Putri; Ratnawati, Kusuma (Strategic Management Business Journal, 2024)
Research background: The current consumption model tends to be irresponsible. Consumers do not have sufficient knowledge regarding environmental impacts, including waste management. Purpose of the article: The objective of this research is to identify the effects of green perceived value, customer green satisfaction, and green trust on customer green loyalty. As a replication, this research uses a quantitative approach. Methods: The population is consumers of Unilever products in Malang City. According to Hair et al. (2010), the number of samples multiples the research item by 5. Using purposive sampling, 145 people were selected as the respondents. The data were tested for validity and reliability and analyzed using multiple regression in SPSS 26. Findings & value added: This study finds that green perceived value, customer green satisfaction, and green trust partially have significant and positive effects on customer green loyalty. Furthermore, this research proves that, although Unilever committed to greenwashing in the past, it does not reduce customer green loyalty. This is probably because green perceived value, customer green satisfaction, and green trust have been established for a long time through the company's green campaigns. Therefore, the company could minimize the negative effect of greenwashing and maintain customer green loyalty. JEL Classification: J28, P36, Q56